1991
DOI: 10.1016/0030-4220(91)90459-p
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations of HIV infection and their management. I. More common lesions

Abstract: Oral lesions are common at all stages of HIV infection. This first of two articles reviews the clinical features and pathogenesis of common oral manifestations of HIV disease (candidiasis, hairy leukoplakia, Kaposi's sarcoma, and HIV-related periodontal disease) and considers current treatment measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 128 publications
3
32
1
6
Order By: Relevance
“…In our study, we found there were no significant differences about socio-demographic data as compared to other research projects all over the world 3,4,5 . Literature review of impact of education level on HIV/AIDS prevalence rate by world food programme (2005) 6 revealed that better educated populations are reacting more strongly than less educated and non educated populations in their responses towards protection through changes in risky sexual behavior.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In our study, we found there were no significant differences about socio-demographic data as compared to other research projects all over the world 3,4,5 . Literature review of impact of education level on HIV/AIDS prevalence rate by world food programme (2005) 6 revealed that better educated populations are reacting more strongly than less educated and non educated populations in their responses towards protection through changes in risky sexual behavior.…”
Section: Discussioncontrasting
confidence: 64%
“…Increased no of oral candidiasis cases can be observed when subjects not under HAART only, are included for the study 13 . Pseudo membranous variety of candidiasis is most commonly found in individuals with HIV infection 3,8,13 , however erythematous candidiasis variant can be more common variety 4 . Very few cases of hyperplastic candidiasis were common finding while angular cheilitis cases were high in some studies 15 .…”
Section: Discussionmentioning
confidence: 99%
“…1 On the other hand a close relation between OC and HL, and severe immunodepression was established. 4,7 Although data regarding the association of viral load and opportunistic oral infections remains conclusive, a higher prevalence of OC in HIV-positive patients whose viral load were greater than 10,000 copies per milliliter 14,15 has been reported. For this reason a prognostic value for OC was recognized.…”
Section: Discussionmentioning
confidence: 99%
“…KS is the most common neoplasm (20-50%) found in HIV-infected individuals (mostly homosexual and bisexual men) (Scully, et al, 1991).Oral lesions are evident in 40% of KS (Greenspan and Greenspan, 1990).Red or purplish macules, papules or nodules appear most frequently on the hard palate (Greenspan and Greenspan, 1990). Unless infected or ulcerated, these lesions do not blanch on pressure (Greenspan and Greenspan, 1990).…”
Section: Clinical Featuresmentioning
confidence: 99%